The Implementation of the Merdeka Curriculum and the Challenges Faced by English Teachers at SMP Sahabat Alam Palangka Raya - Munasikin; Asi, Natalina; Misrita (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This study explored the implementation of the Merdeka Curriculum in English teaching at SMP Sahabat Alam Palangka Raya, focusing on how concept character was integrated, the challenges faced by teachers, and the strategies used to overcome them. The curriculum emphasized student-centered learning, differentiated instruction, and contextual integration. Teachers used methods such as project-based learning, essential material focus, and flexible classroom practices to meet students’ diverse needs. However, the implementation process presented several challenges. These included varied student proficiency levels, limited access to teaching materials, difficulty integrating local content, lack of professional development, time constraints, and low student motivation. To investigate this process, a qualitative case study design was employed, involving classroom observations, in-depth interviews with English teachers, and analysis of teaching documents and student work samples. Findings revealed that teachers adopted various pedagogical approaches aligned with the curriculum, including project-based learning, flexible classroom practices, and an emphasis on essential material tailored to students’ diverse needs. However, several implementation challenges emerged, such as varying student proficiency levels, limited access to appropriate teaching materials, difficulty in integrating local cultural content, insufficient professional development opportunities, time constraints, and low student motivation.